MARINE FISHERIES SECTOR ECONOMIC POTENTIAL AND COASTAL AREA DEVELOPMENT DISPARITIES NORTH SOUTH EAST JAVA - Totok Hendarto (UPT Penerbitan Universitas Jember, 2012)
As an ecosystem, the coastal areas provide a highly productive natural resources and to manage the areas need considering ecological principles to reduce the negative consequences that harm the continuity of its overall development. The issue is how the economic potential of marine fisheries and North South East Java coastal development disparities? Purpose of the study is mapping the economic potential of marine fisheries and North South East Java coastal development disparities. Potential and the role of marine fisheries sector is still not optimal in the economic structure in East Java. There is a largedisparity in the development of North-South coastal areas in East Java. Expected role of local government to further encourage the growth of marine fisheries sector better in the future.